Mapping mining-induced ground fissures and their evolution using UAV photogrammetry - Fu, Yaokun; Wu, Yongzheng; Yin, Xiwen; Zhang, Yanjun (Frontiers in Earth Science, 2023)
Due to its unique geomorphological characteristics, the loess gully region is easy to produce ground fissures under the action of coal mining, destroy the ground infrastructures, induce geological disasters, and threaten the safety of people's lives and property. Therefore, it is particularly important to accurately obtain information about the development of mining-induced ground fissures and study their spatial-temporal evolution mechanism. This paper takes the 1212 working face of a mining area in Yulin City, Shaanxi Province as the research background. Based on UAV remote sensing images and field survey data, we propose a method to extract ground fissures by combining geometric morphology and optical features, and its spatial and temporal evolution mechanism is studied. The study shows that this proposed method significantly reduces noise points and mis-extraction, and the accuracy is more than 80 %, improving the extraction accuracy of ground fissures and making the process more automated. By comparing the extraction accuracy of ground fissures at different flight altitudes, we determine that the optimal flight altitude for the research area is 60m. At the beginning of the working face mining stage, the proportion of low-density areas of ground fissures continues to increase. Some low-density areas transition into high-density areas, which is consistent with the progress of the working face advancement. After the end of the working face retreat, the width of the ground fissures tends to be evenly distributed. The mining-induced ground fissures in the Loess gully and ravine region have good self-similarity. A dynamic development model of ground fissures is constructed to reveal its formation mechanism. The research conclusions can provide a technical support for geological disaster monitoring and land ecological restoration in mining areas.